»I will have mercy on whom I have mercy« The Golden Calf and Divine Mercy in Romans 9–11 and Second Temple Judaism - Barclay, John M. G. 1958- (2010)
5) als grundlegend für die paulinische Hoffnung für Israel und die Völker.
Keywords: Scriptural Narrative; Moses; Grace; Election